2001
DOI: 10.1504/ier.2001.053866
|View full text |Cite
|
Sign up to set email alerts
|

Environmental applications of enzymes

Abstract: Enzymatic processes fall between the two traditional categories of chemical and biological treatment systems since they involve chemical reactions based on the action of biological catalysts. A variety of enzymes from plants and microorganisms have been reported to play important roles in an array of waste treatment applications. Before the full potential of enzymes may be realized, a number of significant issues remain to be addressed. These include: development of low-cost sources of enzymes in quantities th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The use of enzymatic proteins may represent a good alternative for overcoming most disadvantages related to the use of microorganisms (Nannipieri and Bollag, 1991;Karam and Nicell, 1997;Nicell, 2001;Bollag, 2002, Gianfreda andRao, 2004). Enzymes have several beneficial characteristics.…”
Section: Enzymes As Decontaminating Agentsmentioning
confidence: 99%
“…The use of enzymatic proteins may represent a good alternative for overcoming most disadvantages related to the use of microorganisms (Nannipieri and Bollag, 1991;Karam and Nicell, 1997;Nicell, 2001;Bollag, 2002, Gianfreda andRao, 2004). Enzymes have several beneficial characteristics.…”
Section: Enzymes As Decontaminating Agentsmentioning
confidence: 99%
“…In general, it has been suggested that enzymatic wastewater treatment may be most appropriate as either a pre-treatment or polishing step when targeting specific pollutants in combination with a biological process [30] or with physical treatment, such as membrane filtration [32]. Although enzymes offer several advantages over existing treatment methods, their application is still limited due to their current high cost and the specificity of reaction conditions under which they exhibit acceptable activity and stability [33]. In some cases, the application of enzymatic treatment may also be limited due to conditions that result in the inactivation of the enzyme over time.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for using enzymatic systems for colour removal has been recognized for some time (Bajpai and Bajpai, 1994;Karan and Nicell, 1997;Durán and Esposito, 2000;Rodriguez et al, 1999). The reasons for this interest are many (Nicell, 2002). In recent times the rate of introduction of recalcitrant pollutants into the environment is increasing, and it is becoming increasingly difficult to achieve an acceptable degree of removal of these pollutants using conventional chemical and biological processes.…”
Section: The Enzymatic Approach To Dye Transformationmentioning
confidence: 99%